2021
DOI: 10.1186/s13089-021-00235-5
|View full text |Cite
|
Sign up to set email alerts
|

Mean value of B-mode optic nerve sheath diameter as an indicator of increased intracranial pressure: a systematic review and meta-analysis

Abstract: Objectives Timely diagnosis and treatment of increased intracranial pressure can decrease morbidity and prevent mortality. The present meta-analysis aims to determine the mean value of the ONSD measured in patients with various elevated ICP etiologies under different clinical settings, as well as comparing the value of ONSD between patients with and without elevated ICP. Methods This meta-analysis complied with the Preferred Reporting Items for Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…ONSD responds to ICP instantly. The optic nerve sheath has very little risk of plastic deformation or over-distention within the effective range [ 22 , 23 ] and is a very helpful adjunct to other common diagnostic techniques [ 24 ]. Future work is needed to establish consistent techniques and a range of normal ONSD values [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…ONSD responds to ICP instantly. The optic nerve sheath has very little risk of plastic deformation or over-distention within the effective range [ 22 , 23 ] and is a very helpful adjunct to other common diagnostic techniques [ 24 ]. Future work is needed to establish consistent techniques and a range of normal ONSD values [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, some authors found that ONSD was smaller in females, and thus the threshold to define high ICP may be different in females 32 . Several studies tried to define an optimal cutoff value of ONSD in order to predict an intracranial hypertension; but this threshold value is very variable according to the different studies 33 35 . In all, our findings seem to indicate that ONSD values did not reach the threshold observed in those who developed intracranial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was initial evidence from a small observational study on trauma patients [ 57 ], no further studies have been published specifically on the use of ocular POCUS in trauma patients. Diameter of the optic nerve sheath has been correlated with elevated ICPs [ 58 •].…”
Section: Trans-ocular Sonography For Elevated Icpmentioning
confidence: 99%